IMPROVING CHILDREN'S FINE MOTORCY THROUGH PAPER FOLDING ACTIVITIES FOR PAUD TEACHERS AT PKG CA NAI CIBAL - Theresia Alviani Sum; Felisitas Ndeot; Yuliana Atradewi (Universitas Bengkulu, 2021)
PAUD teachers who are members of the PKG Ca Nai Cibal are still low in using and creating a variety of learning media. This results in learning not being stinging and boring for children. One of the activities that can be done so that learning is more intense is the activity of folding paper. This activity can improve the motoric delicacy of children. In the activity of folding paper a lot of media that can be created by children both make rats, cats and various other animals. Through paper folding activities it is hoped that PAUD teachers at PKG ca Nai Cibal will be more creative in creating learning media so that learning is more enjoyable.